The Existency of Salaf Education Institutions in the Middle of Modern Education Flows - Abdul Khamid; Suryawahyuni Latief; Muchamad Chairul Umam (Yayasan Payungi Smart Madani, 2021)
The article was to find out about the existence of salaf pesantren education institutions in the midst of modern education, the role of kiai and ustad salaf pesantren, the education and learning system, and the challenges of salaf pesantren in the midst of modern education. This research used a qualitative approach. Collecting data were obtained through interviews, documentation, and observations. The result show that the role of kyai and ustad in the existence of salaf pesantren in the midst of modern education, while the learning system and teaching are carried out by classical methods. Traditional learning methods used by ustad in transferring lessons involve bandungan, sorogan, memorization method, a characteristic of salaf Islamic boarding school education and teaching. The challenges of the salaf pesantren, show that there werevarious gaps in the students' enrolled in the pesantren, the background of students who are minimal in the need for simplicity in the Salaf Islamic boarding schools, there are still some lack of understanding of the ustad teaching staff, there is still a lack of awareness of discipline, the scientific quality of ustad still lacking with an indication that teachers / ustadz still lacked mastery of the material